2008
DOI: 10.1159/000165170
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Speaker Discrimination Test for Cochlear Implant Users Based on the Oldenburg Logatome Corpus

Abstract: The purpose of the study was to develop a speaker discrimination test for cochlear implant (CI) users. The speech material was drawn from the Oldenburg Logatome (OLLO) corpus, which contains 150 different logatomes read by 40 German and 10 French native speakers. The prototype test battery included 120 logatome pairs spoken by 5 male and 5 female speakers with balanced representations of the conditions ‘same speaker’ and ‘different speaker’. Ten adult normal-hearing listeners and 12 adult postlingually deafene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Yet, the large JNDs observed in this experiment will likely have consequences beyond gender categorization, extending to speaker identification in general. A number of studies have shown that CI listeners had greater difficulty discriminating actual speakers than NH listeners ( Cleary & Pisoni 2002 ; Mühler et al 2009 ). Gaudrain et al (Reference Note 3) investigated that F0 and VTL difference would lead participants to judging they were hearing two different speakers.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the large JNDs observed in this experiment will likely have consequences beyond gender categorization, extending to speaker identification in general. A number of studies have shown that CI listeners had greater difficulty discriminating actual speakers than NH listeners ( Cleary & Pisoni 2002 ; Mühler et al 2009 ). Gaudrain et al (Reference Note 3) investigated that F0 and VTL difference would lead participants to judging they were hearing two different speakers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared to NH participants, CI users had lower accuracy performance in discriminating between unfamiliar talkers' voices (Carmel et al, 2011;Geers et al, 2013), in identifying the gender of voices (Kovačić & Balaban, 2009;Meister et al, 2009) and in learning to identify voices (van Heugten et al, 2014;Vongpaisal et al, 2010). Differences in talker discrimination appear to be more pronounced when tasks used speakers of the same gender (Muhler et al, 2009), or when using varied stimuli within trials (Cleary et al, 2005;Cleary & Pisoni, 2002). CI users also had more difficulty identifying the gender of voices, compared to NH participants (Massida et al, 2013).…”
Section: Comparison To Individuals With Typical Hearingmentioning
confidence: 87%
“…Indeed, findings show that CI users rely more heavily on F0 than VTL compared to NH listeners, who strongly weigh both cues (Fuller et al, 2014;Meister et al, 2009). For instance, CI users are capable of categorizing stimuli from an artificial F0 continuum similarly to NH listeners (Meister et al, 2009) and the discriminability of voices by CI users is correlated to the difference in F0 of the voices, with larger differences in F0 being easier for CI users to discriminate (Muhler et al, 2009). Fu et al (2005) found that CI users can take advantage of temporal periodicity cues to discriminate gender when voices have distinct F0.…”
Section: Role Of Different Acoustic Cuesmentioning
confidence: 94%
“…The Italian Matrix Sentence Test allows adaptive examination and results in noise (Puglisi et al, 2015). In addition, in selected cases, use of logatomes can elucidate auditory functioning in attention and working memory (Muhler et al, 2009;Moradi et al, 2014;Schubotz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%